Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
(a) y = [tex]\frac{-1}{2}[/tex]x - [tex]\frac{3}{2}[/tex]
(b) y = 2x + 3
Step-by-step explanation:
(a) The equation of a line given by points M(x₁, y₁) and N(x₂, y₂) is given by:
y - y₁ = m(x - x₁) -------------------(i)
Where;
m = [tex]\frac{y_2 - y_1}{x_2 - x_1}[/tex] = slope or gradient of the line ---------------(ii)
Given points on the triangle are:
A(2,5)
B(1,-2)
C(-5,1)
To find the equation of line BC, we use the formulas in equations (i) and (ii) where the points of the line are B(1,-2) and C(-5,1) and;
x₁ = 1
y₁ = -2
x₂ = -5
y₂ = 1
==> First get the gradient using equation (ii) as follows;
m = [tex]\frac{y_2 - y_1}{x_2 - x_1}[/tex] = [tex]\frac{1 - (-2)}{-5 -1}[/tex]
m = [tex]\frac{3}{-6}[/tex]
m = [tex]\frac{-1}{2}[/tex]
==> Now, use equation (i) to find the equation of the line as follows;
y - (-2) = [tex]\frac{-1}{2}[/tex](x - 1)
y + 2 = [tex]\frac{-1}{2}[/tex](x - 1)
Multiply both sides by 2
2(y+2) = -1 ( x - 1 )
2y + 4 = -x + 1
2y = -x + 1 - 4
2y = - x - 3
y = [tex]\frac{-1}{2}[/tex]x - [tex]\frac{3}{2}[/tex]
Therefore, the equation of the line is y = [tex]\frac{-1}{2}[/tex]x - [tex]\frac{3}{2}[/tex]
(b) To find the perpendicular line from A to BC, note that
i. two lines are perpendicular if they meet at 90°
ii. the general equation of a line could also be written as y = mx + c where m is the slope and c is the intercept.
iii. when one line has a slope of m, then a perpendicular line to that line will have a slope of [tex]\frac{-1}{m}[/tex]
The equation of line BC is y = [tex]\frac{-1}{2}[/tex]x - [tex]\frac{3}{2}[/tex].
This means that BC has a slope of [tex]\frac{-1}{2}[/tex]
A perpendicular line from A to BC will have a slope of 2.
Now to get the equation of this perpendicular line from A(2, 5) to BC, we use the general equation of a line given in equation (i)
where;
m = 2
x₁ = 2
y₁ = 5
Substitute these values into equation (i)
y - 5 = 2(x - 2)
Solving by simplification gives;
y - 5 = 2x - 2
y = 2x + 3
Therefore, the equation of the perpendicular line is y = 2x + 3
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.